L-type voltage-gated calcium channel agonists mitigate hearing loss and modify ribbon synapse morphology in the zebrafish model of Usher syndrome type 1 - Alaa Koleilat; Joseph A. Dugdale; Trace A. Christenson; Jeffrey L. Bellah; Aaron M. Lambert; Mark A. Masino; Stephen C. Ekker; Lisa A. Schimmenti (The Company of Biologists, 2020)
The mariner (myo7aa−/−) mutant is a zebrafish model for Usher syndrome type 1 (USH1). To further characterize hair cell synaptic elements in myo7aa−/− mutants, we focused on the ribbon synapse and evaluated ultrastructure, number and distribution of immunolabeled ribbons, and postsynaptic densities. By transmission electron microscopy, we determined that myo7aa−/− zebrafish have fewer glutamatergic vesicles tethered to ribbon synapses, yet maintain a comparable ribbon area. In myo7aa−/− hair cells, immunolocalization of Ctbp2 showed fewer ribbon-containing cells in total and an altered distribution of Ctbp2 puncta compared to wild-type hair cells. myo7aa−/− mutants have fewer postsynaptic densities - as assessed by MAGUK immunolabeling - compared to wild-type zebrafish. We quantified the circular swimming behavior of myo7aa−/− mutant fish and measured a greater turning angle (absolute smooth orientation). It has previously been shown that L-type voltage-gated calcium channels are necessary for ribbon localization and occurrence of postsynaptic density; thus, we hypothesized and observed that L-type voltage-gated calcium channel agonists change behavioral and synaptic phenotypes in myo7aa−/− mutants in a drug-specific manner. Our results indicate that treatment with L-type voltage-gated calcium channel agonists alter hair cell synaptic elements and improve behavioral phenotypes of myo7aa−/− mutants. Our data support that L-type voltage-gated calcium channel agonists induce morphological changes at the ribbon synapse - in both the number of tethered vesicles and regarding the distribution of Ctbp2 puncta - shift swimming behavior and improve acoustic startle response.